Analysis of the Effect of Local Wisdom Values on the Competitive Advantage of Tourism Mediated by Promotion in Samosir Regency - Ance Marintan D. Sitohang; Elisabet Siahaan; Yuni Lestari Br Sitepu (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper presents a new and significant contribution to the socio-cultural and economic fields, in particular looking at the relationship of cultural values to the improvement of the community's economy through the tourism business in the Samosir district. The results of the study show that in general the values of local wisdom, namely cultural values, aesthetic values, spiritual values, ethical values, and economic values, have direct and mediated tourism competitive advantages mediated by promotions. However, social value has no significant effect on competitive advantage either directly or mediated by promotion. The use of local cultural wisdom values for tourism competitive advantage is one of the strategies in an effort to increase tourism in Samosir district so that it can improve the economic life of the people of Samosir district.